Effectiveness of first-line antiretroviral therapy and correlates of longitudinal changes in CD4 and viral load among HIV-infected children in Ghana. - Barry, Oliver; Powell, Jonathan; Renner, Lorna; Bonney, Evelyn Y; Prin, Meghan; Ampofo, William; Kusah, Jonas; Goka, Bamenla; Sagoe, Kwamena W C; Shabanova, Veronika; Paintsil, Elijah (BMC infectious diseases, 2013)
Antiretroviral therapy (ART) scale-up in resource-limited countries, with limited capacity for CD4 and HIV viral load monitoring, presents a unique challenge. We determined the effectiveness of first-line ART in a real world pediatric HIV clinic and explored associations between readily obtainable patient data and the trajectories of change in CD4 count and HIV viral load.
Keywords: Adolescent; Anti-HIV Agents; CD4-Positive T-Lymphocytes; Child; Child, Preschool; Drug Resistance, Viral; Female; Ghana; HIV Infections; HIV-1; Humans; Infant; Longitudinal Studies; Male; Prospective Studies; Treatment Outcome; Viral Load